Answer
\( m^3 + 27 = (m + 3)(m^2 - 3m + 9) \) and \( m^3 - 27 = (m - 3)(m^2 + 3m + 9) \).
Solution
It looks like you've provided a set of algebraic expressions involving the variable \( m \). Let's analyze each expression to understand their relationships, especially focusing on polynomial factorization.
### 1. \( m^3 + 27 \)
**Interpretation:** This is a **sum of cubes**, since \( 27 = 3^3 \).
**Factorization:**
The sum of cubes formula is:
\[
a^3 + b^3 = (a + b)(a^2 - ab + b^2)
\]
Applying this to \( m^3 + 27 \):
\[
m^3 + 27 = m^3 + 3^3 = (m + 3)(m^2 - 3m + 9)
\]
### 2. \( (m + 3)^3 \)
**Interpretation:** This is the **expansion of a binomial raised to the third power**.
**Expansion:**
Using the binomial theorem or straightforward multiplication:
\[
(m + 3)^3 = m^3 + 3 \cdot m^2 \cdot 3 + 3 \cdot m \cdot 3^2 + 3^3 = m^3 + 9m^2 + 27m + 27
\]
**Comparison:** This is **not equal** to \( m^3 + 27 \) unless \( m = 0 \).
### 3. \( (m + 3)(m^2 + 9) \)
**Interpretation:** This appears to be an attempted factorization, but it's **incomplete** for \( m^3 + 27 \).
**Multiplication:**
\[
(m + 3)(m^2 + 9) = m^3 + 9m + 3m^2 + 27 = m^3 + 3m^2 + 9m + 27
\]
**Comparison:** This result does **not** match \( m^3 + 27 \) unless \( m = 0 \). Therefore, this is **not a correct factorization** of \( m^3 + 27 \).
### 4. \( (m - 3)(m^2 + 3m + 9) \)
**Interpretation:** This is the factorization of a **difference of cubes**, specifically \( m^3 - 27 \).
**Factorization:**
The difference of cubes formula is:
\[
a^3 - b^3 = (a - b)(a^2 + ab + b^2)
\]
Applying this to \( m^3 - 27 \):
\[
m^3 - 27 = m^3 - 3^3 = (m - 3)(m^2 + 3m + 9)
\]
### **Summary of Correct Factorizations:**
1. **Sum of Cubes:**
\[
m^3 + 27 = (m + 3)(m^2 - 3m + 9)
\]
2. **Difference of Cubes:**
\[
m^3 - 27 = (m - 3)(m^2 + 3m + 9)
\]
3. **Expansion:**
\[
(m + 3)^3 = m^3 + 9m^2 + 27m + 27
\]
4. **Incorrect Factorization Attempt:**
\[
(m + 3)(m^2 + 9) \neq m^3 + 27
\]
### **Key Takeaways:**
- **Sum of Cubes:** \( a^3 + b^3 = (a + b)(a^2 - ab + b^2) \)
- **Difference of Cubes:** \( a^3 - b^3 = (a - b)(a^2 + ab + b^2) \)
- **Cubing a Binomial:** Expanding \( (a + b)^3 \) results in \( a^3 + 3a^2b + 3ab^2 + b^3 \), which is generally different from just \( a^3 + b^3 \).
Ensure you use the correct formulas when factoring or expanding polynomials to avoid inconsistencies.
Reviewed and approved by the UpStudy tutoring team
Explain
Simplify this solution